Ethnomathematics-based Fraction Number E-modules for Prospective Elementary School Teachers - Rena Anriana; Luluk Mauluah; Woro Sri Hastuti; Setiawan Edi Wibowo (Jurnal Ilmiah Sekolah Dasar, 2024)
Fractions are one of the materials that could be clearer to understand for students and prospective MI teacher students. Problems in understanding fractions often arise due to the need for more connection with everyday life. This research aims to develop ethnomathematics-based fractional number e-modules. This research type uses the ADDIE model, which is limited to the development stage. The subjects involved in this study were experts consisting of material experts and media experts, as well as twelve students in second-semester class A as small group test subjects. Data collection in the study was carried out through observation, interviews, and questionnaires with research instruments in the form of module validation sheets, response questionnaires, and test questions. The data obtained were then analyzed using qualitative descriptive and quantitative descriptive analysis. The results obtained from this development research are as follows: (1) the validity of the ethnomathematics-based fractional number e-module was declared valid with the results of the material expert review of 97.93% and the results of the media expert review of 96.66%, (2) the practicality of ethnomathematics-based fractional number e-module based on student responses is declared practical, namely with test results of 90.21% Based on these results, it can be concluded that the ethnomathematics-based fraction number e-module teaching materials developed are valid and practical qualifications.